Physical Activity as Prevention of Chronic Illnesses in Seniors - Mariusz Pietrzak; Katarzyna Sygit; Marian Sygit (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
Physical activity is of key importance in prevention of chronic illnesses, such as cardiovascular disease or metabolicvdiseases. Lack of regular workout in seniors favors the development of these diseases. It is, therefore, advisable to change one’s lifestyle and engage in regular workout in order to reduce the risk of chronic illnesses and disabilities. The aim of this paper is to present how important physical activity is in prevention of chronic illnesses in seniors.